HPCR Manual on International Law Applicable to Air and Missile Warfare / [electronic resource] (Cambridge : Cambridge University Press, 2013)
The HPCR Manual on International Law Applicable to Air and Missile Warfare provides an up-to-date restatement of existing international law applicable to the conduct of air and missile warfare. The HPCR Manual and its associated rule-by-rule Commentary are the results of a six-year endeavor led by the Program on Humanitarian Policy and Conflict Research (HPCR) at Harvard University, during which it convened an international group of renowned legal experts and practitioners to reflect on the current legal framework regulating air and missile warfare from various sources of international law. Through the publication of the HPCR Manual and its associated Commentary, HPCR hopes that legal advisors and military officers will benefit from an in-depth presentation - and interpretation - of international law applicable to military operations involving air and missile warfare. As a result, it is expected that a greater clarity of the law will enhance the protection of civilians in armed conflict.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Air warfare (International law); Humanitarian law